Optimization of the functional concept of the minimum apartment – a study on a selected example. The role of functional details - Tokajuk, Andrzej (Budownictwo i Architektura / Civil and Architectural Engineering, 2023)
The article shows the study about functional concepts of a small apartment. For the research the author has chosen 27,3 m2 apartment from the estate „Za Żelazną Bramą” in Warsaw. The study works on the optimization of minimum apartment model for 1-2 occupants that could meet contemporary standards. The study has proved that the original layout of the apartment can be improved to bring it closer to contemporary requirements. It turned out that improvements and changes mainly concerned dimensions and arrangement of the kitchen and bathroom. Theliving space could also be modified – good results have been obtained by implementing innovative details. The last simulation performed in the research (purely hypothetical) showed that the best optimization result could be obtained by slightly enlarging the basic plan of the apartment.